Mecano-síntese e caracterização de ligas de Ti-Nb-Sn - Muradás, Rodrigo Ricabone (2006)
Mechanical alloying is a powder processing technique involving cold welding, fracturing mechanisms and rewelding of powder particles in a ball mill. The present work applied this technique with the purpose of processing titanium, niobium and tin alloys, through planetary ball mill and attritor mill. The atomic percentages of these elements were varied in six differents ways. The niobium hydrate was used on production of some alloys in study, with the purpose to observe the effects during the milling and on the alloys obtained after sintering. Differences between processing in planetary ball mill and attritor mill, as well the cold welding influences on the kinetic parameters of milling process were approached. The use of niobium hydrate result in a decrease of powders average crystallite size, and an increase of micro hardness of sintered alloys. This work obtained beta titanium alloys and alpha-beta titanium alloys in namometric sizes. The average crystallite size, for milled powders, was 7,6 nm.